Material flow analysis as basis for efficient resource management – the case of aluminium flows in Austria. Issue 6 (12th December 2014) - Buchner, H.; Laner, D.; Rechberger, H.; Fellner, J.
Abstract : Aluminium (Al) consumption growth exceeded those of all other major metals over the last decades. The main driver for this development is the broad range of applications for Al and Al-alloys. As the growth in consumption went along with an increase of anthropogenic stocks and flows of Al, information about material cycles became a crucial issue in terms of resource management. In this study a comprehensive material flow analysis (MFA) of the flows and stocks of Al in Austria for the year 2010 is conducted. The focus of the presented Al balance is on data harmonization and plausibility checks, both based on extensive data and literature research. The stock of Al is derived from bottom-up calculations indicating a total stock of about 260 kg Al per capita with an annual growth of 11 ± 3.1 kg/cap yr in 2010. Total old Al scrap generation is calculated to be 7 ± 1 kg/cap yr. For considering data quality aspects of single input data an adopted method for uncertainty assessment has been applied to the different material flows. This allowed a consistent evaluation of uncertainties within the material flow model. Due to the substantial uncertainties associated with end-of-life Al flows and their significance for secondary Al production in Austria, a better data base is needed in order to evaluate and optimize national Al scrap utilization in secondary production. Therefore, a dynamic MFA model will be built for Austrian Al flows and, in conjunction with the results from the static analyses, will provide a reliable decision basis for future Al resource management.